2018
DOI: 10.1108/jcm-12-2016-2035
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality, consumer ethics, and sustainability: the mediating role of moral identity

Abstract: Purpose The purpose of this study is to examine the mediating role of moral identity on the relations between the independent variable of spirituality and the original consumer ethics scale (OCES) and attitudes towards doing good and recycling practices of the consumer. Design/methodology/approach To test the various hypotheses of the model, the methodology used is that of partial least squares (PLS) path-modelling, which is a variance-based structural equation modelling (SEM). Findings This research revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 85 publications
(116 reference statements)
2
38
1
2
Order By: Relevance
“…Over time, spirituality and mindfulness became important measures for human behavior, especially in the therapeutic, sociological and psychological context. In consumer sciences, the importance of both measures has also been gaining growing attention, with more and more studies focusing on the various benefits and limitations of these two concepts for determining consumer behavior (Rodriguez-Rad and Ramos- Hidalgo 2018, Fischer et al 2017. This is especially true for the concept of spirituality which, until recently, has been strongly associated with religion but is now perceived as a separate psychological construct (Hill et al 2000).…”
Section: The Role Of Spirituality In Food Choice and Dietmentioning
confidence: 99%
“…Over time, spirituality and mindfulness became important measures for human behavior, especially in the therapeutic, sociological and psychological context. In consumer sciences, the importance of both measures has also been gaining growing attention, with more and more studies focusing on the various benefits and limitations of these two concepts for determining consumer behavior (Rodriguez-Rad and Ramos- Hidalgo 2018, Fischer et al 2017. This is especially true for the concept of spirituality which, until recently, has been strongly associated with religion but is now perceived as a separate psychological construct (Hill et al 2000).…”
Section: The Role Of Spirituality In Food Choice and Dietmentioning
confidence: 99%
“…A reliable definition of consumer ethics is ‘the moral principles and standards that guide the behavior of individuals or groups as they obtain, use and dispose of goods and services’ (Muncy & Vitell, , p. 298). Other authors have also made significant contributions to the advancement of consumer ethics from both the theoretical and empirical perspective (Al‐Khatib et al, ; Arli & Pekerti, ; Arli et al, ; Culiberg, ; Rodriguez‐Rad & Ramos‐Hidalgo, Vitell, ). A scale of consumer ethics has been developed from these studies that allows consumers’ ethical beliefs to be observed in relation to their attitude to certain behaviours that could, at best, be considered questionable.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…In Buddhism, for example, it has been associated with corporate environmental responsibility [25] and sustainability [26], both in socio-institutional contexts. On an individual level, religion and spirituality facilitate sustainable behavior through their influence on personal values [27], motivations and goals [20], lifestyles [28], ethics [29,30] and moral identity [31]. Empirically, previous studies have also linked Christian and Buddhist religiousness to greater sustainable consumption [32], intrinsic religious orientation with green product purchases [33] and religiousness/spirituality with sustainable behavior and attitudes (cited in [20]).…”
Section: Aspects Related With Sustainable Behavior: Religion and Unbementioning
confidence: 99%